From Chloroplast Biogenesis to Chlorophyll Accumulation: The Interplay of Light and Hormones on Gene Expression in Camellia sinensis cv. Shuchazao Leaves - Liu, Linlin; Lin, Ning; Liu, Xuyang; Yang, Shu; Wang, Wei; Wan, Xiaochun (Frontiers in Plant Science, 2020)
Chloroplast development and chlorophyll metabolism in model plants have been well characterized. In contrast, the molecular mechanism for chlorophyll biosynthesis in perennial woody crops is still mysterious, especially when referring to the interplay between light and hormone underlying shading effects. Herein we report that the shading-increased accumulation of chlorophylls in Camellia sinensis cv. Shuchazao leaves is at least generated from two aspects: positive changes in chloroplast development and light/hormone regulation of genes and transcription factors involved in the chlorophyll biosynthesis pathway. Under shading condition, tea crop leaves developed abundant chloroplasts with plump size and more intensively thylakoid membranes. For major metabolites in the chlorophyll biosynthesis pathway, Chl a, Chl b, DPP and Mg-Proto IX increased while PBG presented a significant decrease in response to shading. Significant changes were found at the transcription level of regulators in chloroplast biogenesis (GLK1 and LHCB), the structural genes in the chlorophyll biosynthesis pathway (HEMA1, CLH1, PORA and CAO) and the potential components involved in light signaling (PHYA, CRY1, HY5 and DELLAs). Especially, GLK1 and LHCB, two central signal integrators between the nucleus and chloroplast showed clear shading responses, suggesting a crucial role of light in regulating chloroplast development in tea crop leaves. Simultaneously, endogenous phytohormones (auxin, cytokinin and gibberellins) increased significantly at the later stage of shading. The key integrators involved in the hormone signal pathways, EIN3 and EBF1/2 showed increases in response to shading. This implies the changes of hormones, as a part of shading responses itself, play a non-negligible role in modulating chlorophyll biosynthesis in the tea crop. Overall, this data suggests a light-hormone regulation of chloroplast development and chlorophyll biosynthesis in the tea crop is essentially coincident with that present in Arabidopsis. This study provides new insights into the molecular mechanisms that regulate chlorophyll biosynthesis in response to light and hormones in such a commercially important woody plants like the tea crop, which may facilitate the breeding of high-chlorophyll tea cultivars for the improvement of green tea production.